Salivary Oxidative Stress and Antioxidant Capacity in Smokeless Tobacco (Naswar) Users - Ahmad I; Binmadi N; Afridi SG; Aljohani S; Shah I; Saidal A; Shahzad M (Dove Medical Press, 2023)
Iftikhar Ahmad,1 Nada Binmadi,2 Sahib Gul Afridi,1 Suad Aljohani,2 Inayat Shah,3 Ahsan Saidal,4 Muhammad Shahzad3,5 1Department of Biochemistry, Abdul Wali Khan University Mardan, Mardan, Khyber Pakhtunkhwa, 23200, Pakistan; 2Department of Oral Diagnostic Sciences, King Abdulaziz University Faculty of Dentistry, Jeddah, Saudi Arabia; 3Institute of Basic Medical Sciences, Khyber Medical University, Peshawar, 25110, Pakistan; 4Institute of Paramedical Sciences, Khyber Medical University, Peshawar, 24350, Pakistan; 5School of Biological Sciences, Health and Life Sciences Building, University of Reading, Reading, RG6 6AX, UKCorrespondence: Muhammad Shahzad, Institute of Basic Medical Sciences, Khyber Medical University, Hayat Abad Phase 5, Peshawar, 25100, Pakistan, Tel +92 91 9217703, Fax +92 91 9217704, Email shahzad.ibms@kmu.edu.pkBackground: Naswar, a smokeless tobacco product, commonly consumed in Pakistan, is associated with a 10-fold increase in the risk of oral cancer. However, little is known about Naswar's underlying toxicity mechanisms.Objective: The current study aimed to investigate the effects of Naswar use on oral health and salivary parameters.Methods: A case-control study was conducted among Naswar users (n=42) and age-matched healthy controls (n=42) in Pakistan in 2019. Participant data were collected using questionnaires. Decayed, missing, and filled teeth (DMFT) scores were computed during clinical examinations. Unstimulated whole saliva was collected to assess salivary flow rate, pH, and salivary total oxidative stress (TOS)/total antioxidant capacity (TAC) using commercially available kits. Participants' oral health parameters were compared between cases and controls using ANOVA.Results: No significant differences were observed between the two groups in terms of age, oral health, and hygiene practices and mean DMFT score. Mean salivary pH and the salivary flow rate was significantly (p< 0.001) higher in Naswar users (7.7 and 0.71 mL/minute, respectively) than in non-users (6.95 and 0.52 mL/minute, respectively). Although TOS and TAC were not significantly different between the groups, Naswar users generally had a higher TOS (51.6± 42 μmol/L) and lower TAC (0.55± 0.18 mmol/L) than non-users (TOS 45.5± 38.2 μmol/L and TAC 0.57± 0.17 mmol/L). Correlational analysis also revealed a significant positive correlation between DMFT score and Naswar use duration (r=0.796, p< 0.001) and the number of dips/units consumed each day (r=0.515; p< 0.001).Conclusion: Habitual Naswar use is associated with increased salivary flow rate, pH, and TOS, and reduced TAC levels in Pakistani adults compared to non-users. The pro-oxidant changes may contribute toward deleterious effects of Naswar use including oral cancer.Keywords: salivary flow rate, salivary pH, oxidative stress, antioxidant capacity, oral health